Hubungan Perilaku dan Kondisi Lingkungan Rumah dengan Kasus Tuberkulosis - Musadah Musadah; M. Bagus Qomaruddin; Sri Widati (Journal of Telenursing (JOTING), 2023)
This study aims to look at the relationship between behavioral factors and home environmental factors in tuberculosis cases in the city of Surabaya. The method used in this study was a cross-sectional study with 54 patients. The chi-square analysis was performed to see the relationship between behavioral factors and the home environment and tuberculosis cases. The results showed that there was a significant relationship between temperature (p value=0.000), humidity (p value=0.000), ventilation (p value=0.000), type of floor (p value=0.030), and density (p value=0.030) with TB case. Meanwhile, the lighting variable (p value=0.054) and behavior (p value=0.055) had no significant relationship with TB cases. TB cases can be prevented by minimizing risk factors in the home environment and healthy behavior. This study concludes that counseling regarding risk factors should be carried out, reminding and advising people with symptoms of TB or contact with TB patients to check themselves at a health center or health facility. Keywords: Environment, Behavior, Tuberculosis